Sentinel lymph node biopsy in patients with breast cancer ycT4N0M0 after neoadjuvant drug therapy - M. B. Kurbanova; M. A. Frolova; F. Kh. Shidakova; V. A. Amosova; K. V. Gagulaeva; M. A. Margusheva; E. V. Yangirova; A. V. Petrovskiy (ABV-press, 2024)
Sentinel lymph node biopsy is an effective clarifying diagnostic method that is actively used in various malignancies, including breast cancer. The effectiveness of this method has led to a potential expansion of the standard indications for its use. This article is devoted to the study of the effectiveness of sentinel lymph node biopsy based on world literature data regarding the use of ycT4N0M0 in patients with breast cancer after neoadjuvant drug therapy.